SEARCH FOR DARK MATTER SATELLITES USING FERMI-LAT - Ackermann, Markus; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2012)
Numerical simulations based on the ACDM model of cosmology predict a large number of as yet unobserved Galactic dark matter satellites. We report the results of a Large Area Telescope (LAT) search for these satellites via the gamma-ray emission expected from the annihilation of weakly interacting massive particle (WIMP) dark matter. Some dark matter satellites are expected to have hard gamma-ray spectra, finite angular extents, and a lack of counterparts at other wavelengths. We sought to identify LAT sources with these characteristics, focusing on gamma-ray spectra consistent with WIMP annihilation through the b (b) over bar channel. We found no viable dark matter satellite candidates using one year of data, and we present a framework for interpreting this result in the context of numerical simulations to constrain the velocity-averaged annihilation cross section for a conventional 100 GeV WIMP annihilating through the b (b) over bar channel.
CRIS-Team WoS Importer:2020-01-15